Zygomatic anchorage for en masse retraction in the treatment of severe Class II division 1 - (:unkn) unknown (My University, 2005)
An adult female patient who presented with a severe Class II division 1 malocclusion was treated by en masse retraction of upper anterior teeth against zygomatic anchorage. This case report describes the surgical and orthodontic procedures followed during the treatment. En masse retraction of the six anterior teeth by using zygomatic bone anchorage proved to be an efficient method for the correction of a severe overjet problem.
Keywords: Adult; Female; Humans; Malocclusion, Angle Class II; Orthodontics, Corrective; Zygoma; Nickel; Titanium; Orthodontic Appliances; Bicuspid; Dental Alloys; Orthodontic Appliance Design; Tooth Extraction; Cuspid